The problem of healthy food in the tourist industry - Chuyiko, Andrey; Butochkina, Elizaveta (The Journal of V. N. Karazin Kharkiv National University. Series: International Relations. Economics. Country Studies. Tourism, 2018)
The article analyzes the main problems of nutrition of the Ukrainian population, including healthy food in the tourist industry, which is of great importance, taking into account the growing number of trips, the abolition of the visa regime and the gradual Ukraine’s  integration into the European space.  The article analyzes the main approaches to the development of functional products that are as balanced as possible, as well as enriched with various additives of animal and vegetable origin.  Development of such products and recommendations for its implementation in tourist complexes are extremely necessary. The results of the work will contribute to solving an important national problem – preventing a number of diseases and general strengthening of human immunity in a simple way – via food